Composition and abundance of fish species on the coast of Payumb, Merauke City - Sunarni; Modesta Ranny Maturbongs (Sekolah Tinggi Ilmu Pertanian Wuna, 2018)
Coastal area is one of nature ecosystem has high productivity, unique, and have high ecological and economic value. In addition, coastal areas also have important ecological functions such as providers of nutrients, spawning sites and as food for various marine organisms. As a first step in the management of fishery resources that is required information about species composition and abundance of fish in the coast of Payumb area, Merauke City. The objective of the study was to obtain preliminary information on species composition and fish abundance. This research was conducted in October-December 2016, in coastal Payumb city of Merauke. The research station was determined by purposive sampling. The data analysis used is the abundance index (K), index of Shannon-winner diversity, uniformity index (E), and Simpson dominance index (C). The number of fish caught is 529 fish, the value of diversity index is 3.79; value of uniformity index 0.42 and value of index of dominance equal to 0.11.